Strategic management in a vocational training institute: good intentions alone do not ensure a successful outcome - Zaki, Shahid (Henry Stewart Talks, 2023)
Nonprofits, Training, Developing countries, Vision, Mission, Objectives, Strategy, Competitive advantage